# How do you solve #-3(4x-2)=-21#?

By signing up, you agree to our Terms of Service and Privacy Policy

To solve -3(4x - 2) = -21, follow these steps:

- Distribute -3 across the parentheses: -3 * 4x = -12x and -3 * -2 = 6.
- Rewrite the equation: -12x + 6 = -21.
- Subtract 6 from both sides: -12x = -21 - 6.
- Simplify: -12x = -27.
- Divide both sides by -12: x = -27 / -12.
- Simplify: x = 9/4 or x = 2.25.

Therefore, the solution is x = 2.25.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7